Hip joint moments in symptomatic vs. asymptomatic people with mild radiographic hip osteoarthritis. (11th November 2019) - Hall, Michelle; Chabra, Samir; Shakoor, Najia; Leurgans, Sue E.; Demirtas, Hakan; Foucher, Kharma C.
Abstract: Our primary objective was to examine external hip joint moments during walking in people with mild radiographic hip osteoarthritis (OA) with and without symptoms and disease-free controls. Three groups were compared (symptomatic with mild radiographic hip OA, n = 12; asymptomatic with mild radiographic hip OA, n = 13; OA-free controls, n = 20). Measures of the external moment (peak and impulse) in the sagittal, frontal and transverse plane during walking were determined. Variables were compared according to group allocation using mixed linear regression models that included individual gait trials, with group allocation as fixed effect and walking speed as a random effect. Participants with evidence of radiographic disease irrespective of symptoms walked 14–16% slower compared to disease-free controls (p = 0.002). Radiographic disease without symptoms was not associated with any altered measures of hip joint moment compared to asymptomatic OA-free controls once speed was taken into account (p ≥ 0.099). People with both mild radiographic disease and symptoms had lower external peak hip adduction moment (p = 0.005) and lower external peak internal rotation moment (p < 0.001) accounting for walking speed. Among angular impulses, only the presence of symptoms was associated with a reduced hip internal rotation impulse (p = 0.002) in the symptomatic group. Collectively, our observations suggest that symptoms have additional mechanical associations from radiographic disease alone, and provide insight into potential early markers of hip OA. Future research is required to understand the implications of modifying walking speed and/or the external hip adduction and internal rotation moment in people with mild hip OA.